Restorative Justice sebagai Upaya Pemulihan Kerugian Negara dalam Tindak Pidana Penghindaran Pajak dan Penggelapan Pajak - Mardian Putra Frans; Alma Aulia Shafa Purbowo; Ade Tesalonika Tobing; Amanda Vala Batara Rundu Padang (Simbur Cahaya, 2025)
Tax evasion and tax avoidance crimes directly reduce state revenue and significantly hinder public funding. Conventional criminal sanctions, such as imprisonment and fines, are considered ineffective as they fail to ensure restitution and may even increase state expenses due to prison costs. This study aims to examine the effectiveness of the restorative justice approach as an alternative solution in the enforcement of tax criminal law. The research uses a normative legal method, relying on statutory analysis and relevant legal literature. Findings reveal that the application of restorative justice, as regulated under Article 44B of the General Provisions and Tax Procedures Law (UU KUP) and supported by the Harmonization of Tax Regulations Law, offers a strategic mechanism for recovering state losses through penal mediation between taxpayers and tax authorities. This approach aligns with the principle of ultimum remedium, where criminal punishment serves as a last resort after administrative efforts fail. The study concludes that restorative justice not only facilitates more efficient restitution but also enhances voluntary tax compliance. Therefore, it is necessary to establish specific regulations and technical guidelines to implement this mechanism more systematically